2020
DOI: 10.1121/10.0001020
|View full text |Cite
|
Sign up to set email alerts
|

Source localization in the deep ocean using a convolutional neural network

Abstract: In deep-sea source localization, some of the existing methods only estimate the source range, while the others produce large errors in distance estimation when estimating both the range and depth. Here, a convolutional neural network-based method with high accuracy is introduced, in which the source localization problem is solved as a regression problem. The proposed neural network is trained by a normalized acoustic matrix and used to predict the source position. Experimental data from the western Pacific ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…For source ranging, CNNs are built to learn the mapping relationship between the sound data and the source distance. Applications using CNNs for underwater acoustics [9,10] take advantage of the ability of CNNs to exploit the correspondence between sound field features and source location through training. Most CNN-based source localization methods can be roughly separated into regression tasks and classification tasks.…”
Section: Classic Cnns For Source Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For source ranging, CNNs are built to learn the mapping relationship between the sound data and the source distance. Applications using CNNs for underwater acoustics [9,10] take advantage of the ability of CNNs to exploit the correspondence between sound field features and source location through training. Most CNN-based source localization methods can be roughly separated into regression tasks and classification tasks.…”
Section: Classic Cnns For Source Localizationmentioning
confidence: 99%
“…Various studies have found that ML achieved lower error in source ranging than MFP, especially in complex ocean environments with low SNR [5][6][7]. In addition, progressively increasing network architectures, such as FNN [5,6], TDNN [7,8], CNN [9,10], ResNet [11][12][13], and Inceptions [10], are applied to underwater acoustic localization to mine deep features and decouple sound source information from the underwater acoustic environment. This application of ML to source ranging has been demonstrated to achieve good localization results in both synthetic and experimental data sets collected on the sea.…”
Section: Introductionmentioning
confidence: 99%
“…First, this method utilizes the deep neural network (DNN), a purely data-driven approach, to extract features from acoustic data for automatic depth estimation. Recently, many studies present applications of neural networks (NNs) to the underwater acoustic field, such as target localization [16][17][18] , classification [19][20][21][22] etc. According to the simulation and experimental results of the preceding literature, a well-trained NN has a competitive performance in comparison to conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Various deep learning (DL) based researches have been conducted in many applications such as image processing, signal detection, and estimation theory. DL-based SLs also VOLUME 4, 2016 have been studied [17][18][19][20][21][22][23][24][25][26]. The DLSLs were implemented by a deep neural network (DNN) or a convolutional neural network (CNN) with preprocessed data [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%